2009
DOI: 10.1039/b906961e
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and electron density analysis of hydrogen dissociation of protonated benzene

Abstract: The electronic structure of the benzenium cation, [C6H7]+, the simplest intermediate of electrophilic aromatic substitution reactions, was analyzed in terms of the properties of electron densities obtained from multiconfigurational quantum theoretical methods. The indirect C-H coupling constants and the physical contributions to their values were calculated and rationalized in terms of the electron delocalization between the quantum topological atoms in the molecule. The evolution of the electronic structure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…The study in reference [49] showed a relationship between the Fermi contact contribution of calculated coupling constants J C H and the electron delocalization index (C,H) . The computation of the average J C H yielded a value of 30 Hz in good agreement with the experimental value of 26 Hz.…”
Section: Benzenium Cationmentioning
confidence: 96%
See 3 more Smart Citations
“…The study in reference [49] showed a relationship between the Fermi contact contribution of calculated coupling constants J C H and the electron delocalization index (C,H) . The computation of the average J C H yielded a value of 30 Hz in good agreement with the experimental value of 26 Hz.…”
Section: Benzenium Cationmentioning
confidence: 96%
“…For instance, while the equilibrium structure of the complex [C 6 H 6 ... Br 2 ] has the Br 2 molecule close to the rim of the aromatic ring, the system [C 6 H 6 ... NO + ] has the electrophile in top of the center of the benzene molecule [70]. Figure 11 and it has been demostrated that they correspond to saddle points in the PES of C 6 H 7 + [49]. In spite of the fact that the structures in Figure 11 are not minima of the PES of C 6 H 7 + , the topological analysis of these systems [49] along with that of the benzenium cation in subsection 3.2.1 provides information about the changes in the electronic delocalization along the prototype mechanism of an EAS (Figure 3).…”
Section: Electron Delocalization In Complexesmentioning
confidence: 96%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7] Most rearrangement reactions also involve at least one disruption of a bond. [8][9][10][11][12][13] Such bond dissociations are mainly of "chemical" nature and are characterized by electron redistribution [14][15][16][17] through availability of more favorable bonding partners or through external driving forces such as environmental conditions (solvent or temperature). [18][19][20] Furthermore, many atmospheric reactions are also of this type.…”
Section: Introductionmentioning
confidence: 99%